KARAKTERISTIK INKLUSI FLUIDA DALAM MINERALISASI EMAS DI DAERAH LUMBAN JULU, TOBASA, SUMATRA UTARA - Harahap, B. H; Abidin, H. Z. (Pusat Survei Geologi, 2012)
Fluid inclusions study have been conducted in the Lumban Julu area, Tobasa Residence, North Sumatra Province, in the frame work research of programs on metallogeny in the Bukit Barisan zone, North Sumatra segment. Samples analyzed are derived from quartz veins associated with gold mineralization. Metal content of the veins are 12 -131 ppm Cu, 13 - 495 ppm Pb, 8-183 ppm Zn, 2-407 ppm Ag and 0,01-1,85 ppm Au. These quartz veins are milky-white to transparent, prismatic shape and crustiform banding, colloform in texture, containing quartz and several other minerals such as chlorite, clay, epidote and opaque. Fluid inclusions within the quartz host form negative crystals, made up of two components (bi-phase) consisted of liquid and vapor. The liquid phases consist of primary and secondary inclusions and occur within quartz crystal and fractured zone. Liquid Fluid inclusion measurement shows that homogenization temperature can be divided into high-T (326 to >400°C) and low-T (135-262)°C. This hydrothermal fluid is rich in water with low salinity (- 0.28 – (- 1.36) % NaCl equivalent). The data confirm that boiling processes took place when mineral was deposited. Therefore, it is concluded that mineralization processes in the area comprise two systems of mineral depositions, firstly associated with high-T with mesothermal system at ± 1600 m depth and the second one associated with ephythermal system at ± 550 m depth.Key word: fluid inclusion, quartz, epithermal, Tobasa